Examining the Acceptance of Artificial Intelligence in Writing Publications Among Senior High School Teachers in Singkawang - Urai Salam; Aunurrahman; Warneri; Haratua Tiur Maria; Venny Karolina (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
This study explored the acceptance of Artificial Intelligence (AI) in writing publications among senior high school teachers in Singkawang, adopting the Technology Acceptance Model (TAM) as a framework. The research aimed to comprehend teachers' attitudes toward AI integration in their writing practices. AI, including tools such as Google Translate, Grammarly, QuillBot, ChatGPT, and Elicit, offers multifaceted benefits, enhancing writing productivity, providing real-time feedback, and assisting in language translation. The study involved 30 teachers, utilizing the final version of TAM to assess Perceived Usefulness, Perceived Ease of Use, Attitude toward Usage, and Behavioral Intention to Use. Results revealed a moderate level of acceptance, with 83.3% falling into the medium category. Descriptive statistics underscore positive perceptions, indicating that teachers recognize AI's potential benefits, yet qualitative insights are needed to explore barriers and variations in acceptance levels. Despite concerns of over-reliance and potential biases, AI tools significantly contribute to writing efficiency, accessibility, and democratization of information. The study recommends future research to investigate specific AI tool impacts and individual experiences for a more comprehensive understanding of AI acceptance dynamics among Singkawang teachers.